Potential applications and mechanisms of natural products in mucosal-related diseases - Lin, Wang; Ruishi, Xie; Caijiao, Xu; Haoming, Luo; Xuefeng, Hua; Jiyou, Yao; Minqiang, Lu; Shuo, Zhou; Ming, Zhu; Dongyang, Li; Xiaoxue, Fang (Frontiers in Immunology, 2025)
The mucosal barrier serves as a crucial defense against external pathogens and allergens, being widely distributed across the respiratory, gastrointestinal, urogenital tracts, and oral cavity. Its disruption can lead to various diseases, including inflammatory bowel disease, asthma, urinary tract infections, and oral inflammation. Current mainstream treatments for mucosa-associated diseases primarily involve glucocorticoids and immunosuppressants, but their long-term use may cause adverse effects. Therefore, the development of safer and more effective therapeutic strategies has become a focus of research. Natural products, with their multi-target and multi-system regulatory advantages, offer a promising avenue for the treatment of mucosal diseases. This review summarizes the potential applications of natural products in diseases of mucosal barrier dysfunction through mechanisms such as immune modulation, inflammation inhibition, tight junction protein restoration, and gut microbiota regulation, with the aim of providing insights for the exploration of novel therapeutic strategies.